Coastal zones of the Baltic Sea in the Anthropocene: Current state and the impact of climate change - Maren Voss; Peter Holtermann; Soeren Ahmerkamp; Damian Leonardo Arévalo Martínez; Bronwyn Cahill; Manita Chouksey; Joachim W. Dippner; Jörg Dutz; Peter Feldens; Jacob Geersen; Kaja Gentsch; Mayya Gogina; et al. (Estuarine, Coastal and Shelf Science, 2025)

Sorption of Organic Micropollutants to an Agricultural Soil: Effect of Ionic Strength, Cation Valence and pH - Mogens Thalmann; Linus Neubert; Sondra Klitzke; Aki Sebastian Ruhl; Andre Peters (Water, Air, & Soil Pollution, 2025)
Organic micropollutants (OMP) can enter agricultural soils via irrigation with reclaimed water. To better assess ecological risks associated with water reuse, a profound knowledge on the sorption of OMP to soils and how it is affected by varying matrix properties is essential. This study evaluates the sorption characteristics of ten OMP — including pharmaceuticals (carbamazepine, diclofenac, primidone, sulfamethoxazole, valsartan acid), artificial sweeteners (acesulfame, saccharin), and the corrosion inhibitor benzotriazole — in an agricultural soil under variable ionic strength (0, 0.03, and 0.3 mol L −1 ), cation valence (Na + vs. Ca 2+ ), and pH conditions (equilibrium pH vs. pH 7.5). In batch experiments, sorption of most OMP showed a bell-shaped response to increasing ionic strength (IS) with CaCl 2 , with peak sorption observed at moderate IS (0.03 mol L⁻1) and reductions at higher IS, suggesting cation bridging effects and competition dynamics. Additionally, anionic OMP exhibited significantly reduced sorption at higher pH (7.5) due to increased electrostatic repulsion. Linear sorption coefficients (K d ) varied by up to a factor of six across treatments, with stronger effects observed in the topsoil layer, caused by higher organic carbon content. Altogether, the findings of this study highlight the need to consider solution chemistry and specific matrix effects to improve the prediction quality of OMP transport and retention in agricultural soils. The results underline that grouping OMP solely by charge may not suffice for risk assessment, as sorption behaviors are highly substance and soil-specific. Graphical Abstract

Seroprevalence of hepatitis E virus (HEV) in humans living in high pig density areas of Germany - Andi Krumbholz; Sebastian Joel; Paul Dremsek; Anne Neubert; Reimar Johne; Ralf Dürrwald; Mario Walther; Thomas H. Müller; Detlef Kühnel; Jeannette Lange; Peter Wutzler; Andreas Sauerbrei; et al. (Medical Microbiology and Immunology, 2014)